The fig botany, production and uses - Sarkhosh, Ali; Yavari, Alimohammad; Ferguson, Louise (Botany, production and uses., 2022)
"This book provides a comprehensive review of fig growing from a scientific and horticultural perspective, covering botany, production, processing, health, and industrial uses"--